La crisi: aspetti economici e sociali. (The crisis: social and economic aspects) - Alberto Quadrio Curzio (Moneta e Credito, 2010)
The article contains the introduction to the meeting on the financial crisis held in February at the Accademia dei Lincei, by Alberto Quadro Curzio, president of the division of Moral Sciences of the Accademia. The introduction deals with three main topics: a brief account of the crisis, the relevance of a distinctively European and Italian approach to political economy, the historical development within the Accademia of a critical and constructive thought in the field of the socio-economic sciences.